Valorization of Toxic Weed Lantana camara L. Biomass for Adsorptive Removal of Lead - Vipin Kumar Saini; Surindra Suthar; Chaudhari Karmveer; Kapil Kumar (Journal of Chemistry)
Valorization of Lantana camara L., which is a recognized invasive plant, as a potential source of activated carbon is proposed in this study. Its stem and leaf have been utilized for the preparation of activated carbon (ACL and ACS) by following acid-impregnation technique, followed by thermal treatment. The developed activated carbon samples were characterized for their structural and surface related properties by low-temperature nitrogen adsorption isotherm, SEM techniques, and pHPZC method. The samples show reasonable high surface area and pore volume; nonetheless, these properties are higher in case of ACL as compraed to ACS. Both of these samples developed negative charge on their surface due to acid treatment that resulted in an increase in adsorption at pH > 5. The batch adsorption studies on these samples shows the Pb(II) ion adsorption capacities of ACL and ACS were 36.01 and 32.24 mg·g−1, respectively, at 25°C. The kinetics of adsorption with both the sample systems follow the pseudo-second-order model, whereas the experimental equilibrium isotherm data of ACL and ACS were explained by Freundlich and Langmuir models, respectively. For these samples, the HCl shows maximum desorption with which the recycling test on these samples shows that ACS has better recycling potential over ACL samples.